Treatment and survival of patients with insular thyroid carcinoma: 508 cases from the National Cancer Data Base. Issue 6 (4th February 2016) - Pezzi, Todd A.; Sandulache, Vlad C.; Pezzi, Christopher M.; Turkeltaub, Ashley E.; Feng, Lei; Cabanillas, Maria E.; Williams, Michelle D.; Lai, Stephen Y.
Abstract: Background: Insular thyroid carcinoma (ITC) is a rare but aggressive thyroid malignancy. Methods: Patients with ITC ( n = 508) reported to the National Cancer Data Base from 1998 to 2012 were evaluated for patient, tumor, and treatment characteristics and outcomes. Results: Compared to papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC), patients with ITC cancer were older, more often were men, had larger tumors, were more likely to present with distant metastasis, were less likely to have an R0 resection, more likely to receive external beam radiation and chemotherapy, and had significantly worse survival. Multivariate Cox regression identified age >65 years (hazard ratio [HR] = 1.53), presence of at least 1 comorbidity (HR = 1.80), positive lymph nodes (HR = 1.67), the presence of metastasis (HR = 2.73), positive margins (HR = 2.48), and radioactive iodine therapy (HR = 0.63) as significant and independent predictors of survival in ITC. Conclusion: Treatment recommendations should incorporate the use of radioactive iodine after complete surgical resection and clearance of involved nodal basins. © 2016 Wiley Periodicals, Inc. Head Neck 38: 906–912, 2016